The effect of chronic DOAC treatment on clinical outcomes of hospitalized patients with COVID‐19. Issue 9 (22nd June 2021) - Aslan, Burhan; Akyüz, Abdurrahman; Işık, Ferhat; Çap, Murat; İnci, Ümit and Kaya, İlyas and Karahan, Mehmet Zülküf and Aktan, Adem and Bilge, Önder and Özbek, Mehmet and Altıntaş, Bernas and Boyraz, Bedrettin
Abstract: Background: Recent findings indicate that thrombosis is one of the underlying pathophysiology and complication of COVID‐19 infection. Therefore, the prognosis of the disease may be more favourable in people who were under oral anticoagulant treatment before the COVID‐19 diagnosis. This study aims to evaluate the effects of chronic DOAC use on ICU admission and mortality in hospitalized patients due to COVID‐19 infection. Method: Between 1 September and 30 November 2020, 2760 patients hospitalized in our hospital due to COVID‐19 were screened. A total of 1710 patients who met the inclusion criteria were included in the study. The patients were divided into two groups as those who use DOAC due to any cardiovascular disease before the COVID‐19 infection and those who do not. Results: Seventy‐nine patients were enrolled in the DOAC group and 1631 patients in the non‐DOAC group. Median age of all study patient was 62 (52‐71 IQR) and 860 (50.5%) of them were female. The need for intensive care, in‐hospital stay, and mechanical ventilation were observed at higher rates in the DOAC group. Mortality was observed in 23 patients (29%) in the DOAC group, and it was statistically higher in the DOAC group ( P = .002). In the multivariable analysis, age (OR: 1.047, CI: 1.02‐1.06, P < .001), male gender (OR: 1.8, CI: 1.3‐2.7, P = .02), lymphocyte count (OR: 0.45, CI: 0.30‐0.69, P < .001), procalcitonin (OR: 1.12, CI: 1.02‐1.23, P = .015), SaO2 (OR: 0.8, CI: 0.77‐0.82, P < .001) and creatinine (OR: 2.59, CI: 1.3‐5.1, P = .006) were found to be associated with in‐hospital mortality. DOAC treatment was not found to be associated with lower in‐hospital mortality in multivariable analysis (OR:1.17, CI: 0.20‐6.60, P = .850). Conclusion: Our study showed that the use of DOAC prior to hospitalization had no protective effect on in‐hospital mortality and intensive care need in hospitalized COVID‐19 patients.